2016
DOI: 10.22159/ajpcr.2016.v9i6.13628
|View full text |Cite
|
Sign up to set email alerts
|

Anredera Cordifolia Leaves Fraction as an Anti-Hyperlipidemia

Abstract: Objective: The objective of this research was to evaluate reduction of blood cholesterol level by fraction extracts of binahong (Anredera cordifolia) on male Wistar rats. Methods: The rats were given high fat food every day for 3 months and pure cholesterol on week 0, 3, 7 and 11.  After that each binahong fraction (n-hexane fraction, ethyl acetate fraction and water fraction) with doses of 50 mg/kg bw, 100 mg/kg bw, 200 mg/kg bw were given orally for 3 weeks and observed for lipid profile on day 21.   Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Screening of alkaloids showed also negative results (Kumalasari & Sulistyani 2011;Garmana et al 2014;Sukandar et al 2016b;Kaunang & Semuel 2017) or positive ones only for Dragendorff's reagent, with negative results for Bouchardat's, Wagner's, and Mayer's reagents (Basyuni et al 2017). Some authors found negative results in the screening test for tannins (Kumalasari & Sulistyani 2011;Elya et al 2015;Lestari et al 2015Lestari et al , 2016Sukandar et al 2016b) whereas some obtained positive results (Ekaviantiwi et al 2013;Rahmawati et al 2013;Garmana et al 2016;Sukandar et al 2016c;Kaunang & Semuel 2017;Pitaloka & Sukandar 2018). Polyphenols (Kumalasari & Sulistyani 2011;Sukandar et al 2016b, c;Basyuni et al 2017;Pitaloka & Sukandar 2018) and glucoside (Astuti et al 2011;Elya et al 2015) were also detected in screening tests.…”
Section: Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Screening of alkaloids showed also negative results (Kumalasari & Sulistyani 2011;Garmana et al 2014;Sukandar et al 2016b;Kaunang & Semuel 2017) or positive ones only for Dragendorff's reagent, with negative results for Bouchardat's, Wagner's, and Mayer's reagents (Basyuni et al 2017). Some authors found negative results in the screening test for tannins (Kumalasari & Sulistyani 2011;Elya et al 2015;Lestari et al 2015Lestari et al , 2016Sukandar et al 2016b) whereas some obtained positive results (Ekaviantiwi et al 2013;Rahmawati et al 2013;Garmana et al 2016;Sukandar et al 2016c;Kaunang & Semuel 2017;Pitaloka & Sukandar 2018). Polyphenols (Kumalasari & Sulistyani 2011;Sukandar et al 2016b, c;Basyuni et al 2017;Pitaloka & Sukandar 2018) and glucoside (Astuti et al 2011;Elya et al 2015) were also detected in screening tests.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Phytochemical screening was positive for flavonoids, saponins, steroids/terpenoids, and alkaloids (Ekaviantiwi et al 2013;Rahmawati et al 2013;Elya et al 2015;Lestari et al 2015Lestari et al , 2016Sukandar et al 2016c;Pitaloka & Sukandar 2018). Screening of alkaloids showed also negative results (Kumalasari & Sulistyani 2011;Garmana et al 2014;Sukandar et al 2016b;Kaunang & Semuel 2017) or positive ones only for Dragendorff's reagent, with negative results for Bouchardat's, Wagner's, and Mayer's reagents (Basyuni et al 2017).…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It goes by several names: cheng shan chi in China, Madeira vine in England, heartleaf Madeira vine in Europe, and simply Madeira vine in South America. Binahong, also known as gondola, is a typically utilized hedge plant in Indonesia that has been there for quite some time; nevertheless, the exact date of its discovery is unknown [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Anredera cordifolia, often known as the binahong plant, is medicinal. According to anecdotal evidence, the binahong plant can alleviate various physical ailments, including but not limited to rheumatism, aches and pains, bruises, swollen glands, post-operative skin sensitivity, and cuts and scrapes [25]. Among the compounds found in binahong leaves are alkaloids, polyphenols, triterpenoids, saponins, and essential oils.…”
Section: Introductionmentioning
confidence: 99%